2022
DOI: 10.1021/acs.jpcc.2c02984
|View full text |Cite
|
Sign up to set email alerts
|

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds?

Abstract: Hydrogen bonds impact many material properties due to the bond directionality and collective strength. For them to exist, the atoms connected to hydrogen should possess high electronegativity, the distance between the interacting atoms should be less than their van der Waals radii, and there should be a charge transfer between them. In hybrid perovskites, the impact of hydrogen bonds is ascribed to several phenomena. Among them are the effect of passivation at the surface, structural stability of the mixed cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Recalling now that a hydrogen bond can be defined as an interaction between H and a multipole potential of a neighboring atom, we estimate it from the energy of the H–Br electrostatic interaction scriptE H 0.1 eV (for more details, see ref ). This value is in reasonable agreement with previous estimates , of the energy of the H–Br hydrogen bond, illustrating that the proposed here molecular probe can provide important insight into the existence of hydrogen bonding in HOIPs. , …”
supporting
confidence: 92%
See 1 more Smart Citation
“…Recalling now that a hydrogen bond can be defined as an interaction between H and a multipole potential of a neighboring atom, we estimate it from the energy of the H–Br electrostatic interaction scriptE H 0.1 eV (for more details, see ref ). This value is in reasonable agreement with previous estimates , of the energy of the H–Br hydrogen bond, illustrating that the proposed here molecular probe can provide important insight into the existence of hydrogen bonding in HOIPs. , …”
supporting
confidence: 92%
“…This value is in reasonable agreement with previous estimates 50,53 of the energy of the H−Br hydrogen bond, illustrating that the proposed here molecular probe can provide important insight into the existence of hydrogen bonding in HOIPs. 54,55 In conclusion, we propose the semiautonomous A-site cations in HOIPs as a sensitive local probe for optical spectroscopy, which complements the existing techniques such as NMR and NQR. To illustrate the formulated theoretical framework, we have analyzed the average polarizability of the N−H stretching mode extracted by measuring the group refractive index of a bulk single crystal sample of MAPbBr 3 in the mid-IR wavelength range.…”
mentioning
confidence: 94%
“…Although hybrid perovskites have overpowering ionic interactions between the organic and inorganic constituents, the hydrogen bonding has been found responsible for the structural stability of FAPbI 3 , and the appreciable carrier diffusion length in MAPbI 3 . 28 The presence of a hydrogen bonding interaction between the organic cation and the surrounding octahedral cages of PbI 6 4− is a signature of a stable perovskite lattice. In fact, density functional theory calculations and symmetry argument have shown that there are two distinct hydrogen bonding types, namely, αand β-modes, in the tetragonal MAPbI 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By not controlling for other variables, these experiments sometimes lead to contradicting conclusions. For example, in the past two years, Wilks et al indicated the existence of hydrogen–halide interaction in LHP by using density functional theory in conjunction with soft X-ray scattering, whereas a recent paper by Muydinov et al ruled out the existence of hydrogen–halide interaction through Raman spectra and density functional theory …”
Section: Introductionmentioning
confidence: 99%
“…Currently, while most of the efficient and stable LHP solar cells , and light-emitting diodes , are based on formamidinium and/or guanidinium instead of methylammonium when thin film LHP devices were first reported, the debate on hydrogen–halide interaction in LHP materials remains highly active in both simulation ,, and experimental research. ,,, Common methods include varing the cations (Cs ion, methylammonium, formamidinium, and guanidinium) ,,,, and/or the anions (Cl – , Br – , and I – ) ,,, in the LHP composition, pressure, or temperature , to study certain trends as conditions change. However, these methods led to changes in lattice parameter ,, or phase transitions, ,, which impedes the correlation between LHP properties and hydrogen–halide interaction. By not controlling for other variables, these experiments sometimes lead to contradicting conclusions.…”
Section: Introductionmentioning
confidence: 99%